1998
DOI: 10.1073/pnas.95.21.12141
|View full text |Cite
|
Sign up to set email alerts
|

Oligomerization domain-directed reassembly of active dihydrofolate reductase from rationally designed fragments

Abstract: Reassembly of enzymes from peptide fragments has been used as a strategy for understanding the evolution, folding, and role of individual subdomains in catalysis and regulation of activity. We demonstrate an oligomerization-assisted enzyme reassembly strategy whereby fragments are covalently linked to independently folding and interacting domains whose interactions serve to promote efficient refolding and complementation of fragments, forming active enzyme. We show that active murine dihydrofolate reductase (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
268
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(272 citation statements)
references
References 32 publications
(57 reference statements)
3
268
0
1
Order By: Relevance
“…In contrast to the reported PCA version of Rluc (25), we used a homology-modeled structure of Rluc to test different dissection sites. Points of reporter protein dissection into two PCA fragments are generally chosen based on the following criteria: (i) the cut sites are as far as possible from the catalytic site, (ii) the fragments represent recognizable subdomains, (iii) the reporter protein structure can be accessibly folded from fragments fused to interacting proteins, and (iv) the cut sites are in nonstructured regions (19,21,22,33). The structure of Rluc, isolated from the marine ''sea pansy'' R. reniformis, has not been solved; however, a simple Blast search (34) immediately identified several sequences with Ͼ40% sequence identity to the bacterial haloalkane dehalogenases [supporting information (SI) Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the reported PCA version of Rluc (25), we used a homology-modeled structure of Rluc to test different dissection sites. Points of reporter protein dissection into two PCA fragments are generally chosen based on the following criteria: (i) the cut sites are as far as possible from the catalytic site, (ii) the fragments represent recognizable subdomains, (iii) the reporter protein structure can be accessibly folded from fragments fused to interacting proteins, and (iv) the cut sites are in nonstructured regions (19,21,22,33). The structure of Rluc, isolated from the marine ''sea pansy'' R. reniformis, has not been solved; however, a simple Blast search (34) immediately identified several sequences with Ͼ40% sequence identity to the bacterial haloalkane dehalogenases [supporting information (SI) Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We report here a protein-fragment complementation assay (PCA) based on the reporter enzyme Renilla reniformis luciferase (Rluc) that meets these requirements. The PCA strategy allows the detection of protein complex formation by fusing each of the proteins of interest to two fragments of a ''reporter'' protein that has been rationally dissected into two fragments by using protein engineering strategies (18)(19)(20)(21). Binding of the two proteins of interest brings the unfolded fragments into proximity, allowing for folding and reconstitution of measurable activity of the Author contributions: E.S.…”
mentioning
confidence: 99%
“…As proof, a comparative assessment revealed that Ͼ50% of the data generated using Y2H were likely to be false positives (19). To address this shortcoming, several groups have exploited oligomerizationassisted reassembly of split enzymes such as adenylate cyclase (20), ␤-lactamase (Bla) (21), and dihydrofolate reductase (22,23), as well as split fluorescent proteins (24,25). Alternatively, a number of methodologies for detecting interacting proteins in bacteria have been developed that do not rely on interaction-induced complementation of protein fragments, but instead use phage display (26), FRET (27), and cytolocalization of GFP (28).…”
mentioning
confidence: 99%
“…The relative orientation of possible interaction partners distinguishes individual split proteins. For example, split-DHFR is assembled via fusion partners attached to the N-termini of both fragments, 41 whereas hdCM, like split-GFP, 30 is dimerized by a domain fused to the N-terminus of one segment and the C-terminus of the other. Whereas typical split sensors are connected to their probes by flexible linkers, the short, optimized hdCM linkers add a stringent geometric constraint to the mode of dimerization, rendering hdCM particularly suitable for investigations of specifically oriented protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%